Warmer weather linked to tick attack and emergence of severe rickettsioses. - Philippe Parola; Cristina Socolovschi; Luc Jeanjean; Idir Bitam; Pierre-Edouard Fournier; Albert Sotto; Pierre Labauge; Didier Raoult (Public Library of Science (PLoS), 2008)
The impact of climate on the vector behaviour of the worldwide dog tick Rhipicephalus sanguineus is a cause of concern. This tick is a vector for life-threatening organisms including Rickettsia rickettsii, the agent of Rocky Mountain spotted fever, R. conorii, the agent of Mediterranean spotted fever, and the ubiquitous emerging pathogen R. massiliae. A focus of spotted fever was investigated in France in May 2007. Blood and tissue samples from two patients were tested. An entomological survey was organised with the study of climatic conditions. An experimental model was designed to test the affinity of Rh. sanguineus for biting humans in variable temperature conditions. Serological and/or molecular tools confirmed that one patient was infected by R. conorii, whereas the other was infected by R. massiliae. Dense populations of Rh. sanguineus were found. They were infected with new genotypes of clonal populations of either R. conorii (24/133; 18%) or R. massiliae (13/133; 10%). April 2007 was the warmest since 1950, with summer-like temperatures. We show herein that the human affinity of Rh. sanguineus was increased in warmer temperatures. In addition to the originality of theses cases (ophthalmic involvements, the second reported case of R. massiliae infection), we provide evidence that this cluster of cases was related to a warming-mediated increase in the aggressiveness of Rh. sanguineus, leading to increased human attacks. From a global perspective, we predict that as a result of globalisation and warming, more pathogens transmitted by the brown dog tick may emerge in the future.